Replication R script - Wild, Frederik; Stadelmann, David (Multiplicity in Decision-Making of Africa's Interacting Markets: The Functioning of Community Law, the Role of Market Participants and the Power of Regional Judges (MuDAIMa), 2022)
Associated main article: 20220413_DistCoast_article.pdf
Keywords: Geography; Sub-Saharan Africa; Mediation (Statistics); Coastal Proximity; Mediation Analysis; Coastal Countries; Econometric Evidence; Household Survey